Reclaiming "Mydentity": Counterstorytelling to challenge injustice for racially and economically marginalized emerging adults. (21st November 2022) - Pender, Kristen N.; Hope, Elan C.; Sondel, Beth
Abstract: Emerging adulthood is an important period for identity development, the development of sociopolitical beliefs, and establishment of social roles and responsibilities. As a part of this development, counterstorytelling—narrative processes that contrast and challenge dominant oppressive narratives—may be used within counterspaces to facilitate positive identity development and to challenge injustice. In this qualitative study, we analyse interviews with and poetry from 12 emerging adults who were facilitators within a youth critical literacy program to understand how counterstorytelling functions to both facilitate identity development and challenge injustice. We found evidence of two superordinate themes: reclaiming identity, taking ownership of identity through counterstorytelling; and co‐creating a narrative community, collectively building community through counterstorytelling. Findings support counterstorytelling promotes emergent identity development and works as a strategy for challenging injustice and oppression for marginalized emerging adults. Implications for practitioners and future research are discussed.